Straffansvar för annans självmord? - En straffteoretisk granskning av det svenska rättsväsendets syn på självmord och uppmuntran till självmord - Najafi Nassab,Cornelia (2017)
The purpose of this essay is primarily to examine how the Swedish criminal law considers the situation where a person persuades another to kill oneself. Furthermore, the essay aims more generally to investigate the legislator ́s ambition about what actions that should be criminalized and why suicide barely is treated in the judicial. Today, suicide or attempted suicide does not constitute a crime according to Swedish law. Therefore, responsibility for complicity toanother’s suicide can’t be actualized, since it requires assistance to an illegal action. Despite about 1500 suicides a year, the judiciary takes no action and no one has ever been burdened with criminal liability for another's suicide. Ignorance, shame and myths about the mental illnesses that in 90-95 % of the cases causes suicide could be the reason for this. By investigating where the mental illness is derived from, a person who through psychological violence gave rise to the mental ill health could theoretically be charged with criminal responsibility for the suicide. It is unclear how a conviction could be expelled practically, since liability for example assault requires that one can prove a causality between the psychological violence and the mental illness to the extent that it is put beyond reasonable doubt. If the mental illness causes suicide, one has to prove a further causality between the violence and the death. Criminal responsibility for murder or for involuntary manslaughter requires that the decedent committed an unintentional suicide and that the encouraging person have used the deceased as a tool in order for the person to die. Responsibility for unlawful compulsion also requires that psychological violence causes suicide and that the deceased before its death didn’t suffer from any mental illness. Conclusively it can be noted that there are a number of different crimes that, at least theoretically, may become applicable when a person encourages another to commit suicide. Although, the proof would probably not often live up to the evidentiary requirement and criminal liability would hardly be actualized in practice.
Keywords: Straffrätt; Självmord